Immunogenicity of the Recombinant Cryptococcus neoformans HSP70, a Potential Candidate for Developing an ELISA Kit - Shima Safaei; Hossein Rezvan; Roohollah Fateh; Mohammad Khalifeh Gholi (Pasteur Institute of Iran, 2020)
Introduction: Cryptococcus neoformans is an encapsulated fungal pathogen that causes life-threatening meningoencephalitis in immunocompromised patients. This yeast secretes several potent immunogenic proteins by secretory vesicular mechanisms, such as HSP70 chaperone. Methods: The PCR-amplified HSP70 gene was cloned into a PET-28a(+) expression vector. The purified recombinant HSP70  (rHSP70) was evaluated by western blotting using an anti-His Tag-HRP antibody and then used for immunization of a rabbit. The serum of the immunized rabbit was tested against the whole lysate of C. neoformans in ELISA. Results: The antibodies in the rabbit's serum recognized lysate of C. neoformans yeast. The highest antibody levels were achieved after the third booster injection. Conclusion: The rHSP70 showed to be a reliable candidate for the designing and development of an ELISA kit for early detection of cryptococcosis, and to screen a large number of specimens.